Analysis of gallium nitride-based optical microring resonator with doped polymer grafting material - Hazura Haroon; Muhammad Syafiq Ramli; Siti Khadijah Idris; Anis Suhaila Mohd Zain; Hanim Abdul Razak; Thanigai Anbalagan (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
In this paper, the Gallium nitride-based optical microring resonator (OMR) filter with polymer grafting material (PMMA) coating was designed and optimized to predict its potential as a wavelength filtering device. The optimization was focused on the design parameters such as polymer thickness, gap separation variation, and the bus and ring waveguide widths. The target is to achieve the best output in terms of insertion loss (IL) and Extinction Ratio for wavelength-division multiplexing (WDM) applications, specifically for the use of the C-Band network. Upon completion, it was found that the optimized design was a ring radius of 10 μm and PMMA thickness of 0.055 μm, with the bus waveguide width of 800 nm and the output bus waveguide of 800 nm giving the observed IL of 0.07 dB and 87.3% extinction rate.